2018
DOI: 10.1038/s41598-018-32446-7
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of multicopper oxidase CueO G304K mutant: structural basis of the increased laccase activity

Abstract: The multicopper oxidase CueO is involved in copper homeostasis and copper (Cu) tolerance in Escherichia coli. The laccase activity of CueO G304K mutant is higher than wild-type CueO. To explain this increase in activity, we solved the crystal structure of G304K mutant at 1.49 Å. Compared with wild-type CueO, the G304K mutant showed dramatic conformational changes in methionine-rich helix and the relative regulatory loop (R-loop). We further solved the structure of Cu-soaked enzyme, and found that the addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Escherichia coli that are activated by addition of exogenous copper [21][22][23]. In addition to classical T1 Cu and T2/T3 Cu sites, these enzymes can fix additional labile coppers in the M rich domain allowing the electron transfer from the substrate to the T1 Cu [24][25][26][27][28][29]. We recently performed an in-depth electrochemical study of the intra-and inter-electron transfers using the LAC of Thermus thermophilus HB27 (Tt-LAC) immobilized on different electrodes [23].…”
Section: Actually T Thermophilus Lacs Belong To the Mco Group Including The Copper Efflux Oxidase Cueo Ofmentioning
confidence: 99%
“…Escherichia coli that are activated by addition of exogenous copper [21][22][23]. In addition to classical T1 Cu and T2/T3 Cu sites, these enzymes can fix additional labile coppers in the M rich domain allowing the electron transfer from the substrate to the T1 Cu [24][25][26][27][28][29]. We recently performed an in-depth electrochemical study of the intra-and inter-electron transfers using the LAC of Thermus thermophilus HB27 (Tt-LAC) immobilized on different electrodes [23].…”
Section: Actually T Thermophilus Lacs Belong To the Mco Group Including The Copper Efflux Oxidase Cueo Ofmentioning
confidence: 99%
“…The modi cation analysis of CopA by mass spectrometry showed that the loss of Cu( ) in the culture condition reduced the CopA modi cation, the position of the modi cation changed, and nally the protein activity decreased. One explanation is that the addition of Cu( ) induced further conformational changes in the R-loop and methionine-rich helix as a result of the new Cu-binding sites on the enzyme's surface (Wang et al 2018). These observations well explain the copper dependence of CopA oxidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent structural and functional studies found the activity of MCO mutant is higher than wild-type MCO. The reason is that dramatic conformational changes in methionine-rich helix and the relative regulatory loop (R-loop) have occurred (Kataoka et al 2007; Wang et al 2018). Amino acid changes affect the redox potential and steric hindrance of copper ion binding conserved sites (Li et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intracellular conditions may be significantly different from known in vitro optimal conditions for BliLacc and CueO therefore this should be taken into account when designing a whole-cell biocatalyst. Recently, a set of CueO mutants, including G304 K, with increased laccase and the reduced cuprous oxidase activity have been generated [47]. The crystal structure mutated versions of E. coli CueO revealed the importance of methionine-rich helix and the relative regulatory loop and their interaction and movements when the enzyme is Cu-soaked for the access of the substrate, opening the possibility to further design specific substrate-binding mutants [47,48].…”
Section: Discussionmentioning
confidence: 99%